Does Weather Sharpen Income Inequality in Russia? - Vladimir Otrachshenko; Olga Popova (Review of Income and Wealth, 2021)
Using subnational panel data, this paper analyzes how hot and cold extreme temperatures and precipitation affect economic activity and income distribution in Russia. We account for the intensity of exposure to extreme temperatures by analyzing the impacts of both single and consecutive days with extreme temperature, i.e., heat waves and cold spells, and examine several labor market channels behind those effects. We find that consecutive extremely hot days decrease regional GDP per capita but do not affect income inequality. Poor regions are affected by extreme temperatures relatively more than rich regions. These effects occur because of reallocation of labor from employment to unemployment, an increase in prices in poor regions, and to some extent because of changes in the industrial employment structure, while relative wages are not affected. Extremely cold days, both single and consecutive, as well as extreme precipitation have a limited impact on economic activity and income distribution.
Keywords: 330; interregional inequality; income distribution; heat waves; extreme temperature; Russia